Níveis de 25-hidroxivitamina D3 em pacientes com vitiligo - Cappelletti, Taciana (2018)
Vitiligo is a disease of autoimmune etiology and is associated with other autoimmune diseases, such as thyroid disease. The presence of more than one autoimmune disease in a single patient is called polyautoimmunity. Several studies link hypovitaminosis D with autoimmunity, but knowledge about its levels and its relationship to vitiligo and associations is limited. There are no Brazilian studies on this subject. It is suggested that monitoring these levels could identify individuals at greater risk for the development of polyautoimmunity. To evaluate the prevalence of hypovitaminosis D and association with polyautoimmunity in patients with vitiligo who were treated at the dermatology outpatient clinic of a tertiary hospital. A cross-sectional study with clinical examination, photographing, and measurement of 25-hydroxyvitamin D3 levels (25 (OH) D3) was performed. RESULTS: We included 43 patients with vitiligo. The majority were female (n = 27, 62.8%). The mean age of the patients was 49.26 (± 16.15) years. The mean 25 (OH) D3 was 32.74 ng / mL (± 11.35), and deficiency levels were found in 11.6% (n = 5) and insufficiency in 32.6% (n = 14 ) of the participants. Ten patients (23.3%) had another autoimmune disease, the most frequent being hypothyroidism (n = 4). When the relationship between the variables was evaluated, the patients with hypovitaminosis D had more autoimmune diseases, were female, white and outdoor workers. However, these associations were not statistically significant. Our data corroborate with the literature that shows a higher prevalence of hypovitaminosis D in patients with vitiligo. We did not find association between hypovitaminosis D and polyautoimmunity reported by other investigators.